Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 42174 by lucha116 last updated on 19/Aug/18

cos^2 3xcos2x−cos^2 x=0

cos23xcos2xcos2x=0

Answered by tanmay.chaudhury50@gmail.com last updated on 19/Aug/18

(((1+cos6x)/2))cos2x−(((1+cos2x)/2))=0  cos2x+cos2x.cos6x−1−cos2x=0  cos2x.cos6x=1  2cos2x.cos6x=2  cos8x+cos4x=2  cos4x=k  2k^2 −1+k−2=0  2k^2 +k−3=0  2k^2 +3k−2k−3=0  k(2k+3)−1(2k+3)=0  (2k+3)(k−1)=0  k−1=0  k=1  cos4x=1=coso  4x=2nΠ  x=((nΠ)/2)

(1+cos6x2)cos2x(1+cos2x2)=0cos2x+cos2x.cos6x1cos2x=0cos2x.cos6x=12cos2x.cos6x=2cos8x+cos4x=2cos4x=k2k21+k2=02k2+k3=02k2+3k2k3=0k(2k+3)1(2k+3)=0(2k+3)(k1)=0k1=0k=1cos4x=1=coso4x=2nΠx=nΠ2

Commented by lucha116 last updated on 20/Aug/18

thks

thks

Terms of Service

Privacy Policy

Contact: info@tinkutara.com